The carotenoids of shrimps (Decapoda: Caridea and Dendrobranchiata) cultured in China. Issue 5 (7th September 2018) - Su, Fang; Huang, Bo; Liu, Jianguo
Abstract: We compared the carotenoids in tissues of various organs from four shrimps cultured in China, Penaeus monodon Fabricius, 1978, Fenneropenaeus chinensis Osbeck, 1765, Litopenaeus vannamei Boone, 1931, and Exopalaemon carinicauda Holthuis, 1950 . The carotenoid levels vary greatly depending on the species and the tissues sampled, with the highest levels found in the cephalothorax of L. vannamei (295.20 mg kg –1 ), and the lowest in the abdominal muscle of L. vannamei (2.12 mg kg –1 ). Astaxanthin, mainly esterified (47.69–95.56%), but also unesterified (4.44–52.31%), was the predominant carotenoid and contributed 66.64–95.26% of the total carotenoids in all species. β-carotene, echinenone, canthaxanthin, astacene, zeaxanthin, and some unidentified carotenoids were also detected. All- trans -astaxanthin was the predominant geometrical isomer and 9- cis and 13 -cis were the major cis isomers. Two other isomers, 15- cis and di- cis -astaxanthin, were also detected. The stereoisomers (3 S, 3 'S ) and (3 S, 3' R )-astaxanthin were only observed in E. carinicauda, where (3' S, 3' S )-astaxanthin contributed more than 96% to the total astaxanthin content. In contrast, all three possible stereoisomers were detected in P. monodon, F. chinensis, and L. vannamei and the relative levels of these stereoisomers were similar, 25.37–39.11% of (3 S, 3' S )-astaxanthin, 38.85–52.01% of ( 3S, 3'R )-astaxanthin, and 14.07–29.89 % of (3 R, 3' R )-astaxanthin. The astaxanthin-enriched waste, particularly the cephalothorax generated from L. vannamei, is suggested as a good source of natural astaxanthin available by further processing. These results provide some valuable information on carotenoid characteristics of cultured shrimps, especially the specific configurations of astaxanthin.